Anticonculsant activity of thioureido derivatives of acetophenone semicarbazone - Pandeya S.N.; Mishra V.; Singh P.N.; Rupainwar D.C. (My University, 2025)
A series of thioureido derivatives of acetophenone semicarbazone were synthesized and evaluated for anticonvulsant activity. Some compounds provided significant protection against maximal electroshock (MES) and subcutaneous pentylenetetrazol (scPTZ) induced seizures. The compound (2e) was the most active compound in the series with a dose of 30 mg kg-1 and ED50 23.5 mg kg-1 and equipotent to phenytoin ED50 23.2 mg kg-1. The toxicity of the compounds was assessed by determination of their approximate TD50 and LD50 values in order to have a better assessment of their pharmacological profile and protective index.